Molecular epidemiology of Trypanosoma cruzi I infection in northern Argentina - Macchiaverna, Natalia Paula (2025)
Trypanosoma cruzi I (TcI) infects a broad range of mammalian and triatomine species across the Americas and displays broad genetic diversity. The transmission cycles of TcI remain poorly understood. We investigated whether TcI parasites from Didelphis albiventris opossums were linked to the TcI parasites found in domestic dogs, cats and peridomestic Triatoma sordida from the Argentinean Chaco or were linked to other T. cruzi genotypes in opossums. We analyzed the intergenic region of the spliced leader (SL-IR) of the mini-exon gene sequence from direct triatomine samples and culture isolates from those hosts captured in Pampa del Indio, Amam´a, and Garup´a municipalities. Of 56 sequences analyzed, 29 are original to this study and 27 were available at GenBank. Fifteen TcI genotypes were detected in Pampa del Indio, with at least three sub-groups circulating simultaneously. TcId was mainly linked to D. albiventris and T. sordida, suggesting a sylvatic/peridomestic transmission cycle. TcIa was found in a domestic dog and a cat at the same household, likely originated from an unidentified source. A third sub-group of TcI, closely related to sequences from Brazilian and Misiones (Argentina) opossums, was found inT. sordida. To our knowledge, this is the first report of TcI SL-IR sub-groups in T. sordida. Whether D. albiventris opossums are introducing sylvatic parasites to the peridomicile and T. sordida are getting the TcId-infection there or sylvatic T. sordida specimens are arriving to the peridomicile already infected deserves further research.